2017
DOI: 10.1590/s1984-29612017056
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic effect of thymol and thymol acetate on sheep gastrointestinal nematodes and their toxicity in mice

Abstract: Thymol is a monoterpene and acetylation form of this compound can reduce the toxicity and enhance its biological effects. The objective of this study was to evaluate the effect of thymol and thymol acetate (TA) on egg, larva and adult Haemonchus contortus and the cuticular changes, acute toxicity in mice and the efficacy on sheep gastrointestinal nematodes. In vitro tests results were analyzed by analysis of variance (ANOVA) and followed by comparison with Tukey test or Bonferroni. The efficacy of in vivo test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 39 publications
2
34
0
4
Order By: Relevance
“…In an acute toxicity test in mice, the median lethal dose (LD50) of thymol was 1.35 g/kg when administered in a single oral dose, whereas the LD50 of the essential oil of thyme (containing, mainly, carvacrol, 45.5%; André et al, ) and Thymus broussonetii (36.7% of thymol; Elhabazi et al, ) were reported to be above 4.00 and 4.47 g/kg, respectively. In rats, the orally LD50 of thymol, thyme, and a thymol oil–water emulsion (10%) was 0.98 g/kg (Jenner, Hagan, Taylor, Cook, & Fitzhugh, ), 2.84 g/kg (Basch et al, ), and 2.46 g/kg, respectively (Gad, ).…”
Section: Resultsmentioning
confidence: 99%
“…In an acute toxicity test in mice, the median lethal dose (LD50) of thymol was 1.35 g/kg when administered in a single oral dose, whereas the LD50 of the essential oil of thyme (containing, mainly, carvacrol, 45.5%; André et al, ) and Thymus broussonetii (36.7% of thymol; Elhabazi et al, ) were reported to be above 4.00 and 4.47 g/kg, respectively. In rats, the orally LD50 of thymol, thyme, and a thymol oil–water emulsion (10%) was 0.98 g/kg (Jenner, Hagan, Taylor, Cook, & Fitzhugh, ), 2.84 g/kg (Basch et al, ), and 2.46 g/kg, respectively (Gad, ).…”
Section: Resultsmentioning
confidence: 99%
“…& Sessé ex Benth [259] and Ocimum gratissimum L. [260]. This bioactive compound presents a wide variety of pharmacological properties such as anti-obesity [261], anthelmintic [262], anti-inflammatory [263], hepatoprotective [264] and larvicidal [265].…”
Section: Thymolmentioning
confidence: 99%
“…Estudos mais recentes têm utilizado o teste de motilidade de adultos (TMA) para avaliar o efeito de OE, visto que esses produtos naturais são lipofílicos e apresentam baixo peso molecular, sendo capazes de penetrar na cutícula dos nematoides por difusão transcuticular [6,21], alterando os mecanismos de locomoção [68], além de ocasionar lesões cuticulares [4,5]. Entre os fatores limitantes do TMA, destacam-se a necessidade de eutanasiar um animal infectado com NGI e a manutenção dos nematoides em estufa de CO 2 [4,38].…”
Section: Efeito Anti-helmíntico De óLeos Essenciaisunclassified
“…Carvacrol e timol apresentaram atividade ovicida, larvicida e adulticida sobre H. contortus [4,5,23]. Estudos realizados para avaliar o mecanismo de ação desses monoterpenos em C. elegans demonstraram que esses monoterpenos têm ação sobre receptores de tiramina, inibindo a motilidade e o bombeamento da faringe desse nematoide de vida livre [48].…”
Section: Atividade Anti-helmintica De Compostos Isolados De óLeosunclassified
See 1 more Smart Citation